Strategi Penguatan Pariwisata Halal di Kabupaten Trenggalek - Azella Nosih Octavia; Wahyudi S, M. Sri (JOURNAL OF ECONOMIC AND SOCIAL EMPOWERMENT, 2024)
Indonesia has the potential for natural beauty that can be used as an object of economic growth activities, namely through the tourism sector. Halal tourism is part of the tourism industry that is based on Islamic principles and aimed at Muslim tourists. This study aims to conduct a detailed study of tourism object development strategies, especially focusing on the Halal Tourism development plan. This study used a sample of 30 respondents visiting tourist sites in Trenggalek Regency. This study used the SWOT analysis method and the data obtained came from distributing questionnaires to tourist visitors at three tourist sites in Trenggalek Regency. The results of the IFAS and EFAS score research showed favorable results for increasing halal tourism in Trenggalek Regency. This position is in quadrant 1, which signifies the utilization of strengths and weaknesses (SO) strategies. Which is expected to increase the attractiveness of visitors by improving quality, thus taking advantage of the opportunities available.